2000
DOI: 10.1063/1.481256
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of water on the NaCl(001) surface. II. An infrared study at ambient temperatures

Abstract: Water adsorbed on the (001) face of NaCl under ambient conditions has been studied by infrared spectroscopy. From these measurements, combined with recent Monte Carlo calculations, we find evidence of two structures for the adsorbed water. At low coverages, the water molecules aggregate into islands on the surface. When a critical concentration is reached, multilayer growth becomes favorable, creating a thin film on the surface with properties similar to liquid water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
175
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(195 citation statements)
references
References 50 publications
19
175
0
1
Order By: Relevance
“…Note that 79.1% RH above a 14 nm particle surface is equivalent, after accounting for the Kelvin effect (eq 4), to 67.3% RH (20.0 mbar at 297K) above a bulk NaCl crystalline surface, which has roughly 3 ML of adsorbed surface water. 1 It can be concluded that the thickness of the water film on predeliquesced NaCl particle is quantitatively consistent with measurements done on bulk NaCl after properly accounting for the Kelvin effect.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Note that 79.1% RH above a 14 nm particle surface is equivalent, after accounting for the Kelvin effect (eq 4), to 67.3% RH (20.0 mbar at 297K) above a bulk NaCl crystalline surface, which has roughly 3 ML of adsorbed surface water. 1 It can be concluded that the thickness of the water film on predeliquesced NaCl particle is quantitatively consistent with measurements done on bulk NaCl after properly accounting for the Kelvin effect.…”
Section: Discussionsupporting
confidence: 76%
“…This is consistent with ordered thin films of water on NaCl surfaces under ambient conditions. 1 For water interacting with structures that Figure 7. MD simulation snapshots of varying SDS coverage (Θ SDS ) on SDS/NaCl slabs on (a) crystalline NaCl core and (b) aqueous NaCl solution core.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the range of 50-75% RH, below the DRH of NaNO 3 , NO 2 continues to be generated but at a smaller rate. While the salt is solid under these conditions, it holds significant amounts of surface-adsorbed water [101][102][103][104] which increases ion mobility at the interface and provides some liquid-like character to the surface. These results for NaNO 3 suggest that R NO 2 from KNO 3 would be higher if photolysis experiments were conducted 5% above the DRH rather than 7% below, and hence the data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[42][43][44][45][46] Findings generally indicate that, as humidity increases from 0% RH, water first adsorbs onto surface defect sites or in the form of small 2D islands with partial coverage up to ∼40% RH. 44 Between ∼40-50% RH, coverage increases rapidly to the point where it exhibits hydrogen bonding properties resembling that of bulk water.…”
Section: Discussionmentioning
confidence: 99%